Lo indispensable en la interpretación de un hecho social o de una epoca. Juan Velasco Alvarado y Las Reformas - Cerpa Bustamante, Blanca R. (2020)
This essay tries to show the importance of the historical, sociocultural, therefore economic and political contexts, to fully understand the period under analysis, to appreciate the weight and meaning that it really has within the process of change with the that is linked to you. Regarding Velasco Alvarado, de facto president from 1968 to 1975, the national and global context that allows his government and the reforms he undertook is explained here.